Algorithm for predicting the risk of tuberculosis in children with co-infection of tuberculosis and herpesvirus - Voliansky , Andrii; Smilyanskaya, Maiia; Didorenko , Tetiana; Sukhanova, Lydia; Zosymov, Anatoly; Herasimova, Tetiana (Annals of Mechnikov’s Institute, 2023)
Algorithm for predicting the risk of developing tuberculosis in children with tuberculosis (TB) and herpesvirus co-infection, the essence of which is the ranking of the leading laboratory indicators with the determination of their diagnostic informativeness and risk coefficients (CR), followed by the addition of the sum of the CR points that the patient has at the time of calculation.